THE INFLUENCE OF LEARNING MOTIVATION AND LEARNING CONCENTRATION ON UNDERSTANDING OF MATHEMATICS CONCEPTS - Yayan; Tarpan Suparman; Sri Wulan Anggraeni; Tika Nurjanah; Mahpudin; Ujiati Cahyaningsih (Jurnal Cakrawala Pendas, 2023)
The background of this research is the common understanding of mathematical concepts caused by several factors, including online learning, less optimal learning, students finding mathematics challenging to understand, lack of student motivation in learning, and low levels of student learning concentration. This study aims to determine the effect of learning motivation and concentration on understanding mathematical concepts. The method used is a survey with multiple correlation techniques. The sample was taken by random sampling technique, which consisted of 84 students of class V elementary schools in the Tanjungpura-Tanjungmekar Karawang cluster. The instruments used were questionnaires to measure learning motivation and concentration and tests to gauge understanding of mathematical concepts. Data analysis used multiple linear regression statistics with the help of the SPSS 25 application. The results showed (1) there was an effect of learning motivation and study concentration simultaneously (simultaneously) on understanding mathematical concepts 114,921, (2) there was an effect of learning motivation on understanding concepts of mathematics of 0.786, (3) there is an effect of learning concentration on understanding mathematical concepts of 0.784. This can be interpreted that the higher the learning motivation and concentration of learning, the better the understanding of mathematical concepts; conversely, the lower the learning motivation and concentration, the less good the understanding of mathematical concepts is. In conclusion, students who have good learning motivation and concentration are expected to be able to provide examples to other students in the learning process, which can improve their understanding of mathematical concepts. Penelitian ini dilatarbelakangi oleh rendahnya pemahaman konsep matematika yang disebabkan beberapa faktor di antaranya pembelajaran secara daring, pembelajaran kurang maksimal, siswa menganggap matematika sulit untuk dipahami, kurangnya motivasi siswa dalam belajar serta tingkat konsentrasi belajar siswa rendah. Penelitian ini bertujuan untuk mengetahui pengaruh motivasi belajar dan konsentrasi belajar terhadap pemahaman konsep matematika. Metode yang menggunakan yaitu survei dengan teknik korelasi berganda. Sampel diambil dengan teknik random sampling, yaitu berjumlah 84 orang siswa kelas V sekolah dasar se-gugus Tanjungpura-Tanjungmekar Karawang. Instrumen yang digunakan berupa kuisioner untuk mengukur motivasi belajar dan konsentrasi belajar dan tes untuk mengukur pemahaman konsep matematika. Analisis data menggunakan statistik regresi linier berganda dengan berbantuan aplikasi SPSS 25. Hasil penelitian menunjukkan (1) terdapat pengaruh motivasi belajar dan konsentrasi belajar secara bersama-sama (simultan) terhadap pemahaman konsep matematika sebesar 114,921, (2) terdapat pengaruh motivasi belajar terhadap pemahaman konsep matematika sebesar 0,786, (3) terdapat pengaruh konsentrasi belajar terhadap pemahaman konsep matematika sebesar 0,784. Hal ini dapat diartikan semakin tinggi motivasi belajar dan konsentrasi belajar maka semakin baik pula pemahaman konsep matematika, sebaliknya motivasi belajar dan konsentrasi belajar rendah maka semakin kurang baik pula pemahaman konsep matematika. Kesimpulan, siswa memiliki motivasi belajar dan konsentrasi belajar yang baik diharapkan dapat memberikan contoh kepada siswa yang lainnya dalam proses pembelajaran yang dapat meningkatkan pemahaman konsep matematika.